2014
DOI: 10.1175/waf-d-13-00129.1
|View full text |Cite
|
Sign up to set email alerts
|

Finescale Orographic Precipitation Variability and Gap-Filling Radar Potential in Little Cottonwood Canyon, Utah

Abstract: Finescale variations in orographic precipitation pose a major challenge for weather prediction, winter road maintenance, and avalanche forecasting and mitigation in mountainous regions. In this investigation, groundbased X-band radar observations collected during intensive observing period 6 (IOP6) of the Storm Chasing Utah Style Study (SCHUSS) are used to provide an example of these variations during a winter storm in the Wasatch Mountains of northern Utah. Emphasis is placed on precipitation features in and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 114 publications
(90 reference statements)
3
11
0
Order By: Relevance
“…The bimodality of the Valais data may be explained by the exceptional character of the 2016-2017 winter season with unseasonally high temperatures and perhaps the inclusion of data from early spring notwithstanding our careful selection of the data. Nevertheless, they are comparable to the results from Cluckie et al (2000) in Salford, England, where a bimodal distribution of melting layer heights with peaks at 650 and 1850 m was found. The melting layer tops are also within the limits of the values found by Fabry et al (1994b) in Montreal, which ranged between 200 and 3800 m in spring and 0 and 3900 m in winter.…”
Section: Melting Layer Statisticssupporting
confidence: 88%
See 2 more Smart Citations
“…The bimodality of the Valais data may be explained by the exceptional character of the 2016-2017 winter season with unseasonally high temperatures and perhaps the inclusion of data from early spring notwithstanding our careful selection of the data. Nevertheless, they are comparable to the results from Cluckie et al (2000) in Salford, England, where a bimodal distribution of melting layer heights with peaks at 650 and 1850 m was found. The melting layer tops are also within the limits of the values found by Fabry et al (1994b) in Montreal, which ranged between 200 and 3800 m in spring and 0 and 3900 m in winter.…”
Section: Melting Layer Statisticssupporting
confidence: 88%
“…The melting layer tops are also within the limits of the values found by Fabry et al (1994b) in Montreal, which ranged between 200 and 3800 m in spring and 0 and 3900 m in winter. The observed melting layer depths are thicker than those observed by Cluckie et al (2000) but comparable to the depth ranges reported by Fabry et al (1994b). Similarly to the results in Cluckie et al (2000) and Wolfensberger et al (2016), melting layer thickness seems to be independent of season, climate or topography.…”
Section: Melting Layer Statisticssupporting
confidence: 85%
See 1 more Smart Citation
“…Observational studies suggest that during winter storms, a layer containing high values of vertical shear may often be a feature of high mountain ranges (e.g. Lin et al , ; Garvert et al , ; Neiman et al , ; Campbell and Steenburgh, ). Idealized numerical simulations indicate that a shear layer develops on the windward side of a mountain as a result of strong static stability and/or surface friction.…”
Section: Discussionmentioning
confidence: 99%
“…18a], the Oregon Cascades [Garvert et al (2007), their Fig. 19], and the Wasatch Mountains [Campbell and Steenburgh (2014), their Fig. 21].…”
Section: Discussionmentioning
confidence: 99%